Effect of Body Mass Index on Outcomes of Percutaneous Nephrolithotomy: A Systematic Review and Meta-Analysis - Xu, Yan; Huang, Xiaolin (Frontiers in Surgery, 2022)
Objective The current study aimed to assess the efficacy and safety of percutaneous nephrolithotomy (PCNL) in obese and overweight individuals based on body mass index (BMI). Methods We electronically explored the databases of PubMed, CENTRAL, ScienceDirect, Embase, and Google Scholar databases for all types of comparative studies investigating the role of BMI on PCNL outcomes. Only studies defining obesity as >30 kg/m2 were included. Efficacy outcomes were stone-free rates and operating time while safety outcomes were complications and length of hospital stay (LOS). Results Eighteen studies with 101,363 patients were included. We noted no difference in the stone-free rates after PCNL for morbid obese vs normal BMI patients (OR: 0.78 95% CI, 0.57, 1.08 I2 = 7% p = 0.13), overweight vs normal (OR: 1.01 95% CI, 0.89, 1.15 I2 = 1% p = 0.83) and obese vs normal patients (OR: 1.00 95% CI, 0.87, 1.16 I2 = 0% p = 0.95). PCNL operative time was significantly increased in morbid obese (MD: 9.36 95% CI, 2.85, 15.88 I2 = 76% p = 0.005) and obese patients as compared with normal patients (MD: 2.15 95% CI, 1.20, 3.10 I2 = 0% p < 0.00001), but not for overweight patients. There was no difference in the odds of complications between morbid obese vs normal (OR: 1.26 95% CI, 0.93, 1.72 I2 = 0% p = 0.13), overweight vs normal (OR: 1.11 95% CI, 0.96, 1.28 I2 = 0% p = 0.15), and obese vs normal patients (OR: 1.07 95% CI, 0.91, 1.27 I2 = 0% p = 0.40). LOS was significantly reduced in obese patients (MD: −0.12 95% CI, −0.20, −0.04 I2 = 0% p = 0.004) as compared to normal patients, but not for morbid obese or overweight patients. Conclusion PCNL has similar efficacy and safety in morbidly obese, obese, and overweight patients as compared to normal BMI patients with no difference in the stone-free and complication rates. Evidence suggests that operating time is increased in morbidly obese and obese patients and the latter may have shorter LOS. Systematic Review Registration:https://www.crd.york.ac.uk/prospero/, identifier: CRD42022313599.